Sustained fixation induced changes in phoria and convergence peak velocity. - Eun H Kim (Public Library of Science (PLoS), 2011)
Purpose This study sought to investigate the influence of phoria adaptation on convergence peak velocity from responses located at different initial vergence positions. Methods Symmetrical 4° convergence step responses and near dissociated phoria (measured at 40 cm from the subject's midline) were recorded from six subjects with normal binocular vision using an infrared limbus tracking system with a haploscope. Two different sustained fixations (1° and 16° convergent rotation along the subject's midline) were used to study whether phoria had an influence on the peak velocity of convergence responses located at two initial vergence positions (1° or 'far' steps and 12° or 'near' steps). Results Phoria was significantly adapted after a sustained fixation task at near (16°) and far (1°) (p<0.002). A repeated measures ANOVA showed that convergence far steps were significantly faster than the near steps (p<0.03). When comparing convergence steps with the same initial vergence position, steps measured after near phoria adaptation were faster than responses after far adaptation (p<0.02). A regression analysis demonstrated that the change in phoria and the change in convergence peak velocity were significantly correlated for the far convergence steps (r = 0.97, p = 0.001). A weaker correlation was observed for the near convergence steps (r = 0.59, p = 0.20). Conclusion As a result of sustained fixation, phoria was adapted and the peak velocity of the near and far convergence steps was modified. This study has clinical considerations since prisms, which evoke phoria adaptation, can be prescribed to help alleviate visual discomfort. Future investigations should include a systematic study of how prisms may influence convergence and divergence eye movements for those prescribed with prisms within their spectacles.